WELL TRAP STRUCTURES AND BULK-NANO ENVIRONMENT LUMINESCENCE CENTERS IN CaZnGe2O6:Tb3+ LONG AFTERGLOW PHOSPHOR - Kuan Woo, Boon; Li, Yang; Singh, Surinder P. (Malaysian Journal of Science, 2011)
A long afterglow phosphor CaZnGe2O6:Tb3+ has been prepared by using organic coated luminescence ZnO nanopowder through a high temperature solid-state reaction route. This new CaZnGe2O6:Tb3+ long afterglow phosphor sample emits the Tb3+ green fluorescence 543 nm emission corresponding to 5 D 4 âŸ¶ 7 F 5 transition under UVA 350 nm illumination. The organic coated luminescence ZnO nanopowder serves to construct shallow well trap for the Tb3+ dopant and to minimize electron leakage of well traps. By adjusting the mass ratio of both the bulk ZnO powder (â€‹5-10 nm size), depth of well traps that dictate luminescence and afterglow properties could be controlled. The optimized long afterglow phosphor sample was found to be made of 70% gm-weight of bulk ZnO powder and 50% gm-weight of organic coated luminescence ZnO nanopowder or CaZn0.83Ge2O6:Tb3+ phase compound that exhibit afterglow longevity of longer than 3 hours. Therefore, phosphorescence effect is best explained based upon well trap structures model and structure lattice defects play an important role in influencing persistent luminescence phenomena. (Keywords: Afterglow phosphor, phosphorescence, well trap structure .)